The Factors Affecting Successful Breast-feeding (SBF) - Fateme Mohammadi; Amin Kiani; Sakineh Gholamzadeh; Fariba Asadi Noghabi; Tahereh Sadeghi (Mashhad University of Medical Sciences, 2018)
Background: No comprehensive definition of SBF leads to failure in identification of ineffective breast-feeding and clinical problems, which will end up in early hospitalization of the infants. The study tried to describe the factors affecting SBF by Walker and Avant approach.The quantitative, qualitative, and mixed papers using different approaches in nursing, midwifery, nutrition and medical literature from 1995 to 2017 were reviewed by the researchers using keywords "successful breast-feeding," "infant," and "SBF concept analysis," in databases of Cinahel, PubMed, Scopus, Medline and Google Scholar.Methods: We used Walker and Avant approach in the analysis of the factors affecting successful breast-feeding. Searching for "successful breast-feeding" and "infant" triggered the initial study. Ultimately, 84 sources were selected as the sample of the study. Later, data was classified according to characteristics, effective factors, incidences, consequences, and empirical referents connected with successful breast-feeding.Results: As an interactive process, four main characteristics of SBF were holding the infant while breast-feeding, the method of placing the breast in the infant's mouth, sucking, and milk transmission from mother to the infant. Furthermore, some incidents related to SBF were "posture of the infant while breast-feeding," "breast physiology and anatomy," and "infant's mouth physiology and anatomy." The aftermaths included "infant's behavior when being full," "letting go of the breast," "not responding to sucking reflex," "apparently calm infants," and "lack of pain and discomfort in the breast."Conclusion: The results showed that determining the characteristics, events, and aftermaths of SBF is absolutely essential and important for both clinical and nursing intentions. Indeed, accurate estimation of the concept of SBF ends in identification of the related problems and proposing strategies for solving them.